2004
DOI: 10.1016/j.bbrc.2004.10.190
|View full text |Cite
|
Sign up to set email alerts
|

Mcs2 and a novel CAK subunit Pmh1 associate with Skp1 in fission yeast

Abstract: The Mcs6 CDK together with its cognate cyclin Mcs2 represents the CDK-activating kinase (CAK) of fission yeast Cdc2. We have attempted to determine complexes in which Mcs6 and Mcs2 mediate this and possible other functions. Here we characterize a novel interaction between Mcs2 and Skp1, a component of the SCF (Skp1-Cullin-F box protein) ubiquitin ligase. Furthermore, we identify a novel protein termed Pmh1 through its association with Skp1. Pmh1 associates with the Mcs6-Mcs2 complex, enhancing its kinase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The two proteins were later shown to form an active kinase complex (Buck et al, 1995;Damagnez et al, 1995) and to activate fission yeast CDK1-cyclin-B complexes in vitro (Lee et al, 1999). However, mutations in mcs6, mcs2 or pmh1 (which encodes the RING finger subunit) cause neither a defect in CDK activation nor cell-cycle arrest (Molz and Beach, 1993;Buck et al, 1995;Damagnez et al, 1995;Lee et al, 1999;Saiz and Fisher, 2002;Bamps et al, 2004;Lee et al, 2005).…”
Section: One Cak or Two: The Fission Yeast Variationmentioning
confidence: 99%
“…The two proteins were later shown to form an active kinase complex (Buck et al, 1995;Damagnez et al, 1995) and to activate fission yeast CDK1-cyclin-B complexes in vitro (Lee et al, 1999). However, mutations in mcs6, mcs2 or pmh1 (which encodes the RING finger subunit) cause neither a defect in CDK activation nor cell-cycle arrest (Molz and Beach, 1993;Buck et al, 1995;Damagnez et al, 1995;Lee et al, 1999;Saiz and Fisher, 2002;Bamps et al, 2004;Lee et al, 2005).…”
Section: One Cak or Two: The Fission Yeast Variationmentioning
confidence: 99%
“…There is no convincing evidence of α-tubulin aceltylation in yeast. [36][37][38] An ortholog of the mec-17 gene is not found in either the S. cerevisiae or the S. pombe genome, and the target lysine is conserved in S. cerevisiae but not in S. pombe (data not shown).…”
Section: The Case Of α-Tubulin Acetylationmentioning
confidence: 99%
“…While our manuscript was in review, Bamps et al (2004) also reported that disruption of pmh1 was lethal.…”
Section: A Cdk Linking Gene Expression With Cell Cycle Controlmentioning
confidence: 99%